Road map for policy instruments to be developed for mutually supportive implementation of the Plant Treaty and the Nagoya Protocol in Benin and Madagascar - Bioversity International (2016)
Road map for policy instruments to be developed for mutually supportive implementation of the Plant Treaty and the Nagoya Protocol in Benin and Madagascar Madagascar and Benin have both ratified the International Treaty on Plant Genetic Resources for Food and Agriculture (the Plant Treaty) and the Nagoya Protocol on access and benefit sharing. To date, neither country has put systems in place for their implementation.